PENGUJIAN SURVIVAL JAMUR YANG DIPRESERVASI DALAM AIR DAN PARAFIN CAIR - Suciatmih Suciatmih; Rachmat Rachmat (Research Center for Biology-Indonesian Institute of Sciences, 2005)
A study has been conducted for survival testing of 7 and 7-16 years-preserved fungi in water and liquid-paraffin respectively.Survival testing was done through replanting the preserved fungi in new PDA slant media.The growth observation of fungi was carried out for two weeks long.Each collection number was tested with two replications. Thirteen collection numbers of fungi (Alternaria spp.,Aspergillus spp.,Fusarium spp.,Penicillium spp.,and Trichoderma spp.,)which were preserved for 7 and 8 years long in water and liquid-paraffin respectively were growing again, and the rate of survival were 100%. The survival of the fungi(species and sum of sample were different) which were preserved in liquid-paraffin for 7, 8, 9 and 16 years long were 38,5, 81,5,53,6, and 64,7% respectively.